Effect of Ovariohysterectomy at the Time of Tumor Removal in Dogs with Benign Mammary Tumors and Hyperplastic Lesions: A Randomized Controlled Clinical Trial - Kristiansen, V.M.; Nødtvedt, A.; Breen, A.M.; Langeland, M.; Teige, J.; Goldschmidt, M.; Jonasdottir, T.J.; Grotmol, T.; Sørenmo, K. (Journal of veterinary internal medicine, 2013)
Background Nonmalignant mammary tumors (NMT) are common in intact female dogs. Little is known about the clinical significance of these tumors, and the effect of ovariohysterectomy (OHE) on their development. Hypothesis Ovarian hormone ablation through OHE decreases the risk of new tumors and thereby improves long‐term prognosis for dogs with NMT. Animals Eighty‐four sexually intact bitches with NMT. Methods Dogs were allocated to undergo OHE (n = 42) or not (n = 42) at the time of NMT removal in a randomized clinical trial. Tumor diagnosis was confirmed histologically in all subjects. Information about new tumor development was collected via follow‐up phone calls and recheck examinations. Separate survival analyses were performed with the endpoints new tumor development and death. Cause of death was classified as related or unrelated to mammary tumor. In addition to OHE status, the influence of age, body weight, breed, tumor size, tumor number, tumor duration, type of surgery, and tumor histology was investigated. Results New mammary tumor(s) developed in 27 of 42 (64%) intact dogs and 15 of 42 (36%) ovariohysterectomized dogs (hazard ratio 0.47, P = .022). Nine of the 42 dogs (21%) which developed new tumors were euthanized because of mammary tumor. Survival was not significantly different between the 2 treatment groups. In the intact group, nine dogs subsequently developed ovarian–uterine diseases. Conclusion Ovariohysterectomy performed at the time of mammary tumor excision reduced the risk of new tumors by about 50% among dogs with NMT. Survival was not significantly affected. Adjuvant OHE should be considered in adult dogs with mammary tumors.